Efek Penambahan Belimbing Wuluh (Averrhoa Bilimbi L.) Dalam Ransum Terhadap Performan, Karkas Dan Income Over Feed Cost Ayam Kampung - Rachmat Wiradimadja; Wiwin Tanwiriah; Denny Rusmana (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
Starfruit (Averrhoa bilimbi L.) can serve as an acidifier which can improve digestive enzymes work, suppress the growth of pathogenic microbes, protecting feed from microbial and fungal attack and to improve the palatability of feed. The main objective of this study was to determine the effect of starfruit in the ration on the performance (feed intake, body weight gain, feed conversion), the weight of carcass parts, fatty meats, and income over feed cost. The study used 80 chicks two weeks old village with a complete randomized block design experiment method. The treatment consisted of control diet (P0), and three levels of addition of starfruit (P1 = 0.5%; P2 = 1%; and P3 = 1.5%). Each treatment was repeated 5 times. Rations and water were given adlibitum. The trial period lasts for 30 days. Test performed to determine differences in Duncan.The results showed the addition of up to 5% starfruit into the ration does not affect the performance of chicken and chicken carcass weight parts. The highest value of income over feed cost was achieved by treatment with the addition of 0.5% ration starfruit juice.